How to Drink Like a Royal - Schmid, Albert W. A. (Book collections on Project MUSE., 2020)
"Royalty." A single word that invokes daydreams of champagne, lavish lifestyles, and extravagant parties. In How to Drink Like a Royal, Albert W.A. Schmid offers readers a taste of how the other half lives, with cocktail recipes inspired by some of the world's most famous dynasties. To ensure that you will delight even royal guests, Schmid also provides tips for proper etiquette, such as the requirement to stand if the Monarch is standing and to never, ever try to take a selfie. Discover cocktails like the Golden Doublet, created to celebrate the marriage of England's Princess Anne to Captain Mark Phillips, or the Savoy Royale created for Queen Elizabeth the Queen Mother on her visit to the Savoy Hotel, London. Other recipes give ode to royal families from works of literature, like the Beowulf Cocktail honoring King Hrothgar of the Danes. Even the royalty of the United States is featured through the Hawaiian Martini, an homage to the Hawaiian royal family who reigned from their palaces until 1893. With easy-to-follow glossaries for both royal and cocktail-making terms alongside 180 reciepes for a wide array of drinks that will quench any sort of thirst, How to Drink Like a Royal is an informative and light-hearted manual to help you cultivate your inner prince or princess